What are the Predictive Factors of the Cure and Complication Rates for Midurethral Slings in the Treatment of Stress Urinary Incontinence in Women: A Multicenter and Multivariate Analysis Study - TARCAN, TUFAN (GALENOS YAYINCILIK, 2017)
Objective: Predictive factors that could affect the cure and complication rates of midurethral slings (MUS) in the treatment of stress urinary incontinence (SUI) were investigated. Materials and Methods: A total of 594 women (outside-in transobturator in 285, inside-out transobturator in 91, and retropubic in 218) with SUI and who had undergone MUS were evaluated. The median age was 53.9 (27-82) years. Univariate analyses were done using chi-square test, Student's t-test and the Mann-Whitney U test. Multivariate analyses were done using logistic regression analysis to determine predictive factors affecting cure and complication rates. Results: The mean follow-up time was 48 months. The subjective cure rate was 84% and complication rate was 11.2%. On univariate and multivariate analyses, the cure rate was found to be increased in younger patients [odds ratio (OR): 0.97, 95% confidence interval (CI): 0.95-0.99, p=0.038] and in patients with pure SUI (OR: 2.17, 95% CI: 1.31-3.60, p=0.002). The type of surgery was the only statistically significant parameter affecting the complication rate, which was significantly higher in retropubic MUS procedure (OR: 6.28, 95% CI: 3.51-11.22, p<0.001). Conclusion: MUS is an effective and safe surgical procedure in the treatment of SUI. In this study, age and type of incontinence were the only significant predictive factors affecting the cure rate. Our study suggests that retropubic approach could be considered a risk factor for complication after MUS.
Keywords: Stress urinary incontinence; midurethral sling; transobturator; retropubic; complication; FREE VAGINAL TAPE; RANDOMIZED-CONTROLLED-TRIAL; TRANSOBTURATOR TAPE; SURGICAL-TREATMENT; RISK-FACTORS; FOLLOW-UP; OPERATIONS; OUTCOMES; TVT; PRESSURE